Numerical Simulation of the Diffusion of Fissure Slurry at High Temperature. (2nd March 2022) - Niu, Jiandong; Sun, Yong; Liu, Jianxin; Li, Huimei; Tan, Xiaojun; Han, Ning; Wang, Bin; Qiu, Liangliang
Abstract : Deep-buried tunnel at high-ground temperature is prone to the sudden surge of water when crossing the water-rich formation, resulting in casualties and economic losses. Slurry injection is a common and effective method of governance for addressing this issue. However, there has been little research into pulping at high-ground temperature, with most of the existing research focusing on room temperature conditions. We studied two kinds of slurry commonly used in grouting, cement slurry and cement-sodium silicate slurry. Indoor testing was used in this paper to clarify the effect of temperature on slurry viscosity, and numerical simulation was used to study slurry diffusion in flat cracks at different temperatures. The results showed that in a hydrostatic environment, the spread rate of slurry was independent of temperature and type of slurry. For the same kind of slurry, the higher the temperature, the greater the maximum slurry pressure. The higher the temperature in a flow environment, the faster the slurry diffusion. As the temperature rised, the grouting pressure required for crack sealing decreased at first then rises. In a flow environment, the sealing effect of cement-sodium silicate slurry was superior to that of cement slurry.